Migraine treatment with biological therapies. The state of the art - Krymchantowski, Abouch; Jevoux, Carla; Silva-Néto, Raimundo Pereira (Headache Medicine, 2023)
Migraine is a highly prevalent and debilitating neurological disorder. Most patients do not receive a correct diagnosis and effective treatments. Apart of the few specialists and tertiary centers worldwide, the treatment of migraine is usually symptomatic and prevention, as well as treatments of the underlying mechanisms, are not aimed. It results in frustration and substantial burden. The last few years witnessed the releasing of specific biological therapies, mostly addressing one of the peptides involved in migraine pathophysiology, the calcitonin gene-related peptide (CGRP). Either the small molecules as well as the monoclonal antibodies against CGRP or its canonical receptor have been launched in markets across the globe and represent interesting options for the treatment of migraine. Onabotulinumtoxin A has also been proposed for chronic migraine as well, but not for episodic migraine, based on its unique ability to inhibit the SNARE complex formation and the release of numerous potential mediators of migraine. However, despite the favorable figures on efficacy and tolerability of these compounds, the regulations, and particulars of different countries, regarding the structures and reimbursement of medical care, demonstrated different adhesion profiles of chosen populations to receive these emerging weapons against migraine-imposed suffering. This review addresses the use and characteristics of biological therapies used in migraine treatment.